Functional and Imaging Outcomes of Arthroscopic Simultaneous Rotator Cuff Repair and Bankart Repair After Shoulder Dislocations. (November 2014) - Shields, Edward; Mirabelli, Mark; Amsdell, Simon; Thorsness, Robert; Goldblatt, John; Maloney, Michael; Voloshin, Ilya
Background: Previous studies have investigated outcomes of simultaneous rotator cuff (RC) repair and superior labral injury repair; however, there is limited information in the literature on outcomes of simultaneous RC repair and Bankart lesion repair after acute shoulder dislocations. Purpose: To determine functional and imaging outcomes of simultaneous arthroscopic RC repair and Bankart repair after acute shoulder dislocations and to compare functional outcomes to contralateral, asymptomatic shoulders. Study Design: Cohort study; Level of evidence, 3. Methods: Consecutive patients who underwent arthroscopic simultaneous RC repair and Bankart repair with a minimum of 2 years' follow-up were recruited. All patients had suffered an acute shoulder dislocation. The American Shoulder and Elbow Surgeons (ASES), Constant-Murley, and Short Form (SF)–36 scores were obtained. The affected shoulder also underwent ultrasound imaging to assess the integrity of the RC. Results: Thirteen patients (mean age, 58.8 ± 11.2 years; mean follow-up, 38.5 ± 12.3 months) were recruited. In a comparison of the affected versus unaffected shoulder, there were no significant differences in the mean ASES score (89.7 ± 12.6 vs 95.0 ± 6.7, respectively), mean Constant score (80.5 ± 18.9 vs 86.8 ± 7.9, respectively), or mean abduction strength (15.4 ± 6.4 lb vs 15.4 ± 5.2 lb, respectively) ( P > .05). The mean SF-36 physical component summary was 48.4. According to ultrasound imaging, there were persistent/recurrent full-thickness tears in 4 patients, and 1 patient had a new full-thickness tear. At follow-up, patients with full-thickness RC tears in the affected shoulder compared with their unaffected shoulder showed similar mean ASES scores (90.9 ± 11.8 vs 97.6 ± 4.3, respectively), mean Constant scores (77.8 ± 20.3 vs 84.8 ± 7.2, respectively), and mean abduction strength (11.5 ± 5.3 lb vs 12.6 ± 4.5 lb, respectively) ( P > .05). Conclusion: After simultaneous arthroscopic repair of the RC and a Bankart lesion in patients after shoulder dislocations, the affected extremity had similar functional outcomes compared to the noninjured, asymptomatic side at a mean of 3 years after surgery. Persistent or recurrent RC tears involving the operative extremity were common, but they did not significantly affect functional outcomes in this small study.